Perancangan Sistem Emergency Call untuk Pengendara Bermotor Berbasis Mobile - Amirudin, Nur Said; Aryanto, Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The progress of land transportation, especially motorized vehicles, has a great influence on people's welfare. Currently motorized vehicles have a large contribution to the development of transportation in Indonesia. The increasing number of vehicles always results in problems such as flat tires, running out of petrol or breaking down and the number of these incidents always increases. When problems occur on the highway, drivers always have difficulty finding locations and information about relevant places in order to ask for help with the problems they are facing. This research aims to enable motorized vehicle users to have an Android-based mobile application that is useful for providing location information and related parties to speed up the rescue process. The application that will be developed has a emergency call feature for users to service providers or relevant locations according to the driver's problem. Not only that, this system is also a business platform for those who want to join the merchant feature in it. In this mobile application study, the author will utilize the Google Maps API so that he can search and recommend the nearest place for motorists to seek help. This research was carried out from the analysis, design, implementation, to testing stages.